Food safety, consumption behavior, and personal values: an integrative review - Campos, Rita de Cássia Leal; Vilas Boas, Luiz Henrique de Barros; Brito, Mozar José de (Revista de Administração da UFSM, 2024)
Purpose: To map in international literature how personal values ​​have been addressed in the context of consumer behavior in relation to food safety. Design/methodology/approach: An integrative review was employed as the research method using the Web of Science and Scopus scientific databases. Nineteen empirical articles were selected and classified into five analysis categories: i) cultural context; ii) risk perception and willingness to pay; iii) sustainable consumption; iv) animal welfare; and v) differences among sociodemographic profiles. Findings: The studies focus on identifying personal values that influence attitudes and behaviors related to food safety in food consumption. They seek to understand how these values, reflected in consumer concerns about food safety, affect the categorization of foods as healthy/safe. Practical implications: The understanding of the factors that interfere with consumer relationships is crucial in the context of food safety, as it allows for the enhancement of communication strategies and policies targeted toward the consuming public. Originality/value: This study provides an integrative framework based on the analyzed literature and suggests future research perspectives to advance knowledge on the subject.